Science Process Skills in Education: Bibliometric Analysis and Review - Anis Elliyani; Suryanti Suryanti; Zainul Arifin Imam Supardi; Binar Kurnia Prahani; Hitta Alfi Muhimmah (IKIP Mataram, 2024)
This research aims to view and review published research on Science Process Skills (SPS) in 2020–2023 using VOSViewer. Article data from Google Scholar database journals collected using Publish or Perish. In 2020-2021 the number of articles published experienced a significant increase, but starting from 2022-2023 it experienced a drastic decline. Topics such as science process skills, students, development, effects, models, analysis, and learning have often been discussed by researchers. In contrast to keywords such as correlation, STEM, self efficacy, case, comparison, improvement, argumentation, and POGIL, these are research topics that are rarely researched and too broad to be studied in more depth. The results of the review of the top 10 articles cited tend to examine strategies for mastering science process skills which include experimentation, minds-on, inquiry approaches, discovery learning, strategic manipulation, debate skills, ICT, STEM, student-centered teaching, use of a variety of learning tools, hands-on exercises, group activities, PhET, mobile scientific investigations, guided inquiry, PBL, PjBL, learning cycles, use of learning media, modules and worksheets. The novelty of this research is a bibliometric analysis and review of the latest research in the field of SPS. The implication of this research is contributes and support Kurikulum Merdeka’s science learning outcomes. Future researchers can use these insights to improve science education, helps focus on their studies, and pinpoint SPS research trends.